Good strategy, bad strategy the difference and why it matters - Rumelt, Richard P. (New York Crown Business, 2011)
Good Strategy/Bad Strategy uses fascinating examples from business, nonprofit, and military affairs to bring its original and pragmatic ideas to life. The detailed examples range from Apple to General Motors, from the two Iraq wars to Afghanistan, from a small local market to Wal-Mart, from Nvidia to Silicon Graphics, from the Getty Trust to the Los Angeles Unified School District, from Cisco Systems to Paccar, and from Global Crossing to the 2007?08 financial crisis.
Includes index
Keywords: Strategic planning